Improved chilling tolerance in glasshouse-grown potted sweet basil by end-of-production, short-duration supplementary far red light - Begum, Firdous U.; Skinner, George; Smieszek, Sandra P.; Budge, Simon; Stead, Anthony D.; Devlin, Paul F. (Frontiers in Plant Science, 2023)
Sweet basil is a popular culinary herb used in many cuisines around the world and is widely grown commercially for retail as a live potted plant. However, basil is easily damaged by temperatures below 12 o C meaning plants must be transported from the grower to the retailer in a warm transport chain, adding considerable commercial cost in temperate countries. Improvement of chilling tolerance has been demonstrated in post-harvest crops such as tomato fruits and, indeed, fresh cut basil, by manipulation of the red:far red ratio of light provided to plants throughout the photoperiod and for a significant duration of the growing process in controlled environment chambers. We tested the effectiveness of periodic short-duration end-of-production supplementary far red light treatments designed for use with basil plants grown in a large scale commercial glasshouse for the live potted basil market. Four days of periodic, midday supplementary far red light given at end of production induced robust tolerance to 24 h of 4 o C cold treatment, resulting in greatly reduced visual damage, and reduced physiological markers of chilling injury including electrolyte leakage and reactive oxygen species accumulation. Antioxidant levels were also maintained at higher levels in live potted basil following this cold treatment. RNAseq-based analysis of gene expression changes associated with this response pointed to increased conversion of starch to soluble raffinose family oligosaccharide sugars; increased biosynthesis of anthocyanins and selected amino acids; inactivation of gibberellin signaling; and reduced expression of fatty acid desaturases, all previously associated with increased chilling tolerance in plants.